Mnemonic strategic training increases functional connectivity in amnestic mild cognitive impairment: Results from a randomized controlled trial: Dementia care research (research projects; nonpharmacological)/Therapeutic strategies and interventions. (7th December 2020) - Simon, Sharon Sanz; Hampstead, Benjamin M; Silva, Mariana PN; Duran, Fabio LS; Fonseca, Luciana Mascarenhas; Martin, Maria Da Graça M; Avila, Renata; Porto, Fabio Henrique de Gobbi; Brucki, Sonia Maria Dozzi; Martins, Camila B; Tascone, Lyssandra dos Santos; Amaro, Edson; et al.
Abstract: Background: Previous research showed that mnemonic strategy training (MST) improves cognitive performance in people with MCI, and has been associated with increased brain activation consonant with the cognitive processes engaged by the training, such as, semantic memory, decision‐making, cognitive control, face processing and social cognition. Despite the growing body of literature on MST in MCI, we are not aware of any randomized controlled study that have examined the effect of MST on resting‐state functional connectivity (FC). Therefore, the aim of the present study was to investigate the effect of MST, focused on face‐name associations, on resting‐state FC in older adults with MCI. Method: Twenty‐six amnestic MCI participants were randomized to one of two interventions: MST (N=14) or an Education Program (EP) (N=12). Both interventions were face‐to‐face, and occurred twice a week over two consecutive weeks (i.e., four sessions). Open‐eyes resting‐state functional magnetic resonance imaging (fMRI) was collected at pre‐ and post‐intervention. Nine regions of interest (ROIs) were selected a priori, based on areas that showed activation changes in a face‐name fMRI paradigm after MST (considering the contrast post>pre within the MST group, and in the comparison MST > EP). Changes in FC (post > pre, and pre > post) were examined through ROI‐to‐ROI analysis in the contrasts MST > EP and EP > MST. Analyses were conducted with CONN toolbox 17.f, and significant results were corrected for multiple comparison using false discovery rate (FDR). Result: At post‐intervention, the MST group showed increased FC relative to the EP. Specifically, there was FC increase between the right inferior frontal gyrus (pars triangularis) and three ROIs in the left hemisphere: fusiform gyrus, temporal pole and orbitofrontal cortex. Within group analysis showed that FC increased after intervention only in the MST group, whereas the EP group showed decreased FC. Conclusion: Our findings indicate that MST enhance FC in functionally relevant regions for the training; effects that support a general change in the innate connectivity that are not limited to a task‐specific condition. Our results extent the knowledge on the underlying mechanisms of MST, and may provide neurophysiological evidence of transfer.